2023
DOI: 10.1136/bmj-2022-072098
|View full text |Cite
|
Sign up to set email alerts
|

Estimated impact from the withdrawal of primary care financial incentives on selected indicators of quality of care in Scotland: controlled interrupted time series analysis

Abstract: ObjectiveTo determine whether the withdrawal of the Quality and Outcomes Framework (QOF) scheme in primary care in Scotland in 2016 had an impact on selected recorded quality of care, compared with England where the scheme continued.DesignControlled interrupted time series regression analysis.SettingGeneral practices in Scotland and England.Participants979 practices with 5 599 171 registered patients in Scotland, and 7921 practices with 56 270 628 registered patients in England in 2013-14, decreasing to 864 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…A recent House of Commons report acknowledged that the number of FTE GPs is insufficient and declining, and that access and continuity had declined. 37 It is thus worrying that the findings in the current study, although cross-sectional, suggest that these declines may have adversely affected life expectancy, even before the pandemic.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A recent House of Commons report acknowledged that the number of FTE GPs is insufficient and declining, and that access and continuity had declined. 37 It is thus worrying that the findings in the current study, although cross-sectional, suggest that these declines may have adversely affected life expectancy, even before the pandemic.…”
Section: Discussionmentioning
confidence: 72%
“…The finding in the current study suggests that further research is required into the potential effects of reducing or withdrawing the QOF scheme before any policy decisions. 37 …”
Section: Discussionmentioning
confidence: 99%
“…For researchers, the key implication is to recognise that only using hospital data is likely to seriously under-ascertain many conditions (although it will identify people with more severe disease for some conditions like heart failure), which will particularly matter in studies of multimorbidity or in studies where mental health is important. There are, however, certain circumstances where it is appropriate to use primary care data alone, for example when examining trajectories of workload pressures in primary care [ 39 ] or changes in quality of care in relation to financial incentives offered to general practitioners [ 40 ]. Further research is needed to examine the validity of diagnoses recorded in both primary and secondary care, with accurate estimation of false positive and false negative rates for different choices of data source.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a reanalysis of cluster randomised trials as interrupted time series found that effect estimates were largely concordant [ 36 ]. Rigorous quasi-experimental studies can make important policy contributions where randomisation was not acceptable or feasible, for example, in examining the effects of withdrawing financial incentives on adherence to primary care indicators [ 37 ].…”
Section: Main Textmentioning
confidence: 99%